Pengaruh Tata Letak Terhadap Produksi Harian PT. Perdagangan dan Perindustrian Lembah Karet - Gilang Fernanda; Gesit Thabrani; Muthia Roza Linda (Jurnal Kajian Manajemen dan Wirausaha, 2019)
AbstractProduction becomes an important factor in operating a company whose level of production is stable and in accordance with production targets will make the company survive in competition. To achieve production stability, the layout strategy is one of the important factors that determine the running of the company's production. Distance traveled is a layout indicator that affects the travel distance of raw materials from the storage area to the production area. The per unit labor cost is a layout indicator in the form of costs incurred for each unit in the production process. This study aims to (1) to determine the effect of distance traveled to the production of PT P & P Lembah Karet (2) to find out the effect of unit labor costs on the production of PT P & P Lembah Karet. The analysis used in this study is multiple regression by processing using SPSS software using a 48-week sample of the 2017 production period. The results of this study are (1) Distance Traveled variables that negatively affect the production of PT P & P Lembah Karet (2) unit labor cost variables has a significant negative effect on the production of PT P & P Lembah Karet. Keywords: Production, Layout, Distance Traveled, Unit labor costs.